Features of Functional Dyspepsia in Children of Early Age - Temirov Murodjon Telman o’g’li (Journal of Science in Medicine and Life, 2024)
Today, the Rome Criteria IV revision (2016) is the main consensus document at the international level, which contains section G, which combines the diagnosis of functional disorders in infants and children of the first 4 years of life. Clinical recommendations “Functional disorders of the digestive organs” (FDOP) were created on the basis of the 2016 Rome IV criteria developed by experts of the World Gastroenterological Organization (WGO).